Design of Wide-band Power Amplifier based on Power Combiner Technique with Low Intermodulation Distortion - Mussa Mabrok; Zahriladha Zakaria; Nasrullah Saifullah (International Journal of Electrical and Computer Engineering (IJECE), 2018)
RF power amplifiers are one of challenging blocks in designing radio frequency transceivers, this is due to non-linearity behavior of power amplifiers that leads to inter-modulation distortion. This paper presents the design of wide-band power amplifier which combined with parallel coupled line band pass filter at the input and output of power amplifier to allow the only required frequency band to pass through the power amplifier. Class-A topology and ATF-511P8 transistor are used in this design. Advanced Design System software used as a simulation tool to simulate the designed wide-band power amplifier. The simulation results showed an input return loss (S11) which less than -10dB, and gain (S21) is higher than 10 dB over the entire frequency band and considers as flat as well. The designed amplifier is stable over the bandwidth (K>1). Inter-modulation distortion is -56.919dBc which is less than -50dBc with 10dBm input power. The designed amplifier can be used for the microwave applications which include weather radar, satellite communication, wireless networking, mobile, and TV.